(3GdeUHGM aj Yde GdeaJGMs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s ((3eUWai GdWdGhi GdTGaYi s)
(3ChdgG (B:s
(3hHYOaEf Gddg JYGdi GfRd Ydi QShdg ai GdPcQ Gdecfhf s
(3BNQgG (B:s
(3hbO Bf dfG Cf fJe GdSaQ GdChd ef gPG GdcJGH hGddg GdeSJYGf hGdMeO ddg GdQMje GdQMef GdYXje GdSdWGf s
(3LeY ajg NdGUI SGFQ cJHg acGf MGhjG deaGJjM CHhGH cfhR GdUfGYI GdEdgjIs
(3PcQ GdeDda ai GdhQbI GdCNjQI eDdaGJg ai Yde GdUfYI heQGJHgGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs